Changing fish trade and demand patterns in developing countries and their significance for policy research - Delgado, Christopher L.; Courbois, Claude (International Food Policy Research Institute, 1997)
Trends for major fisheries products are evaluated for the past two decades, using aggregate annual data. Major changes have been propelled by income growth, changes in preferences and health concerns about meat in developed countries, leading to increased consumption of high-valued fisheries items such as shell and filet fish. Developing countries, especially East Asia, are rapidly increasing consumption of lower valued fishery items, and fish-culture is becoming an increasingly important source of food and exports. Developed countries accounted for 85 percent of net world fish imports in 1994, mostly at the high end of the value spectrum, from about twenty countries. In the ten years preceding 1993, the net value of fisheries exports from developing countries went from less than a third of net developing country exports of sugar, beverage crops and tropical specialty products combined, to a level exceeding that total. While real fish prices have remained relatively stable since 1970, real beef prices have declined by 300 percent, suggesting that a rally in meat prices would further accentuate the shift to fish. Current evidence suggests a 15 percent relative strengthening of fish prices to beef through 2020.